2019
DOI: 10.1111/jep.13114
|View full text |Cite
|
Sign up to set email alerts
|

Exploring hospital patient sitters' fall prevention task readiness: A cross‐sectional survey

Abstract: Rationale, Aims, and Objectives: Patient sitters provide one-to-one care for hospital patients at high risk of falls. The study aimed to explore patient sitters' task readiness to assist in fall prevention on hospital wards. Method:We conducted a cross-sectional survey. Respondents were patient sitters working in five hospitals providing medical, surgical, and aged care. The survey was developed using a theory of health behaviour change and used closed and openended items. Qualitative data were analysed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Data from the United States estimate that 700,000 to 1 million patient falls occur in U.S. hospitals annually (LeLaurin & Shorr, 2019); an average of 6.63 falls per 1,000 occupied bed days were reported in the UK (Morris & O'Riordan, 2017); and an average of 33,000 annual fall events—in Australia (Australian Institute of Health & Welfare, 2016). Yet, despite repeated warnings that inpatients' falls represent a major threat to patient safety, their frequency has not decreased (de Jong et al., 2020). Nurses can play a significant role in fall prevention through their regular attendance during 24 hr and consistent contact with patients (King et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Data from the United States estimate that 700,000 to 1 million patient falls occur in U.S. hospitals annually (LeLaurin & Shorr, 2019); an average of 6.63 falls per 1,000 occupied bed days were reported in the UK (Morris & O'Riordan, 2017); and an average of 33,000 annual fall events—in Australia (Australian Institute of Health & Welfare, 2016). Yet, despite repeated warnings that inpatients' falls represent a major threat to patient safety, their frequency has not decreased (de Jong et al., 2020). Nurses can play a significant role in fall prevention through their regular attendance during 24 hr and consistent contact with patients (King et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…15 , 17 , 20 , 21 , 23 , 24 Some studies have shown that PSAs have not received adequate fall prevention training. 14 , 19 , 21 The PSA often does not perform interventions to address the root cause of the problem, such as delirium. Video monitoring, specifically the use of portable cameras with a speaker and a trained technician to directly observe patients from a remote location, serves as an alternative to the PSA.…”
Section: Introductionmentioning
confidence: 99%
“…PSAs, also known as sitters or observation assistants, provide constant direct observation of patients who have cognitive impairments or thoughts of harming themselves or others. [12][13][14][15][16] These patients may experience hallucinations, psychosis, agitation, confusion, impulsiveness, restlessness, disorientation, or delirium, or they may be inclined to remove medical devices such as I.V. lines and catheters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This passive watching role may contribute to an inability to affect real safety outcomes. For example, although AINs in one study perceived falls to be caused by patient behaviour and confusion, they only focussed on decluttering the environment for safety, rather than reducing the risk of falling through enacting individualised psychosocial strategies for reducing stress in the patient and subsequently the severity of their BPS ( de Jong, Weselman, Kitchen, & Hill, 2019 ).…”
Section: Introductionmentioning
confidence: 99%